Meningkatkan Keterampilan Komunikasi Siswa SMP Negeri 4 Banda Aceh Melalui Bimbingan Kelompok Dengan Teknik Bermain Peran - Angga Nugraha; Martunis Yahya; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
The research entitled "Improving Communication Skills of Junior High School 4 Banda Aceh Students through Group Guidance with Role Play Techniques" aimed at looking at improving communication skills of SMPN 4 Banda Aceh students before and after role playing techniques. This research uses Mixed Method approach with action research type. Subjects in this study amounted to 30 people who have low communication skill level. Data collection using closed questionnaire method with scale 1-5 and observation. Research data then analyzed by paired sample t-test. The result of data analysis showed that students' communication skill level improved after being given group guidance by role playing technique with t value equal to 19.385 and sig value. (2-tailed) 0.000 0,05 in cycle 1, then data on cycle II found t value equal to 14.067 and sig value. (2-tailed) of 0.000 0.05 it can be concluded that there is a change in the improvement of students' communication skills when before and after the given action and hypothesis accepted. That is, group guidance with role playing techniques can improve students' communication skills. Based on the observation data shows the improvement of the communication skills of students before and after the action is given, the students have started to appreciate the opinions of others, understand the conversation, issue ideas well, and able to solve the problems that exist when communicating.